From War to Peace in the Balkans, the Middle East and Ukraine - Serwer, Daniel Paul (2019)
This open access book focuses on the origins, consequences and aftermath of the 1995 and 1999 Western military interventions that led to the end of the most recent Balkan wars. Though challenging problems remain in Bosnia, Macedonia, Kosovo, and Serbia, the conflict prevention and state-building efforts thereafter were partly successful as countries of the region are on separate tracks towards European Union membership. This study highlights lessons that can be applied to the Middle East and Ukraine, where similar conflicts are likewise challenging sovereignty and territorial integrity. It is an accessible treatment of what makes war and how to make peace ideal for all readers interested in how violent international conflicts can be managed, informed by the experience of a practitioner